Protein and Energy Intake Assessment and Their Association With In-Hospital Mortality in Critically Ill COVID-19 Patients: A Prospective Cohort Study - Hajimohammadebrahim-Ketabforoush, Melika; Vahdat Shariatpanahi, Zahra; Vahdat Shariatpanahi, Maryam; Shahbazi, Erfan; Shahbazi, Shaahin (Frontiers in Nutrition, 2021)
Background and Aim: It is partially known that nutritional intake could alleviate proteolysis and course of disease severity in COVID-19 patients; however, not enough data is available in this regard. The present study aimed to assess protein and energy intake and their association with in-hospital mortality in critically ill COVID-19 patients. Methods: A total of 126 critically ill COVID-19 patients, ≥ 5 days and a subset of 111 patients in ICU ≥10 days completed the present prospective observational cohort study. Results: Protein and energy intakes on day 5 of ICU admission in survivors were 46 % and 58 % of target values, respectively. These values in non-survivors were 42 % and 50 % of target values, respectively (P< 0.05). In the sample≥ 10 days, protein and energy intakes in survivors reached to 64 % and 87 % of target values, respectively, without statistically significant differences with non-survivors. In the sample ≥ 5 days, Cox proportional hazard regression was adjusted for GLIM, APACHE II, comorbidity, and age; the results indicated that the patients with protein and energy intake lower than 0.59 g/kg/day and 14 kcal/kg/day, had ~ 2 fold mortality hazard (protein: HR, 2.38; 95% CI, 1.40-4.03; P = 0.001 and energy: HR, 2.23; 95% CI, 1.27-3.92; P = 0.005). Conclusion: Actual protein and energy intakes in critically ill patients with COVID-19 are in suboptimal levels compared with goal recommendations in these patients. Moreover, higher amounts of protein and energy intakes in the early acute phase were significantly associated with better survival and lower risk of in-hospital mortality.